Dynamics of Vertical Axis Wind Turbines (Darrieus Type) - A. F. Abdel Azim El-Sayed; C. Hirsch; R. Derdelinckx (International Journal of Rotating Machinery)
A computing package that combines finite element methods for evaluating the resonance frequencies and modes of turbine subcomponents (blade, tower and shaft) together with the aerodynamic calculations for forces and moments taking into consideration the dynamic stall as well as the dynamic response is developed. This method was applied to a realistic VAWT; namely; the PIONEER I built in the Netherlands by Fokker company. A reasonable agreement between the calculated and field results was predicted.